Parental Attitudes Toward Standard Newborn Screening and Newborn Genomic Sequencing: Findings From the BabySeq Study - Armstrong, Brittan; Christensen, Kurt D.; Genetti, Casie A.; Parad, Richard B.; Robinson, Jill Oliver; Blout Zawatsky, Carrie L.; Zettler, Bethany; Beggs, Alan H.; Holm, Ingrid A.; Green, Robert C.; McGuire, Amy L.; Smith, Hadley Stevens; et al. (Frontiers in Genetics, 2022)
Introduction: With increasing utility and decreasing cost of genomic sequencing, augmentation of standard newborn screening (NBS) programs with newborn genomic sequencing (nGS) has been proposed. Before nGS can be integrated into newborn screening, parents’ perspectives must be better understood. Objective: Using data from surveys administered to parents of healthy newborns who were enrolled in the BabySeq Project, a randomized clinical trial of nGS alongside NBS, this paper reports parents’ attitudes regarding population-based NBS and nGS assessed 3 months after results disclosure. Methods: Parental attitudes regarding whether all newborns should receive, and whether informed consent should be required for, NBS and nGS, as well as whether nGS should be mandated were assessed using 5-point scales from strongly disagree (=1) to strongly agree (=5). Parents’ interest in receiving types of results from nGS was assessed on a 5-point scale from not at all interested (=1) to very interested (=5). Survey responses were analyzed using Fisher’s exact tests, paired t-tests, and repeated measures ANOVA. Results: At 3 months post-disclosure, 248 parents of 174 healthy newborns submitted a survey. Support for every newborn receiving standard NBS (mean 4.67) was higher than that for every newborn receiving nGS (mean 3.60; p < 0.001). Support for required informed consent for NBS (mean 3.44) was lower than that for nGS (mean 4.27, p < 0.001). Parents’ attitudes toward NBS and nGS were not significantly associated with self-reported political orientation. If hypothetically receiving nGS outside of the BabySeq Project, most parents reported being very interested in receiving information on their baby’s risk of developing a disease in childhood that can be prevented, treated, or cured (86.8%) and their risk of developing a disease during adulthood that can be prevented, treated, or cured (84.6%). Discussion: Parents’ opinions are crucial to inform design and delivery of public health programs, as the success of the program hinges on parents’ trust and participation. To accommodate parents’ preferences without affecting the current high participation rates in NBS, an optional add-on consent to nGS in addition to NBS may be a feasible approach. Trial Registration ClinicalTrials.gov Identifier: NCT02422511.